Legal Protection for Wives in Joint Property Division After Divorce - Mutiara Far'h Riasya; Moh. Muhibbin; Budi Parmono (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The division of joint property following divorce remains a central issue in Indonesian family law, particularly under the normative framework of the Marriage Law and the Compilation of Islamic Law, which traditionally emphasize equal distribution. Specific Background: In practice, rigid application of a 50:50 division often fails to address situations where one spouse bears a dominant economic role, especially in cases involving wives as primary breadwinners. Knowledge Gap: There is limited doctrinal clarity on how courts should reconcile formal equality norms with factual disparities in economic contribution within marriage. Aims: This study aims to analyze legal protection for wives in joint property disputes where husbands fail to contribute economically, as reflected in Blitar Religious Court Decision Number 1560/Pdt.G/2023/PA.BL. Results: Using a normative juridical method with statutory, conceptual, and case approaches, the study finds that the court allocated 80% of joint property to the wife and 20% to the husband, based on evidence of the wife’s exclusive financial contribution and the husband’s failure to fulfill economic obligations. Novelty: The decision demonstrates judicial recognition that justice in joint property division need not follow a mathematical formula, but may adopt proportional distribution grounded in substantive justice. Implications: This ruling provides an important precedent for strengthening legal protection for wives, affirming that factual economic contributions and vulnerability after divorce must guide equitable resolution of joint property disputes in Indonesian religious courts. Highlights: Judicial reasoning prioritized factual economic roles over formal equal-sharing norms. Proportional allocation was grounded in evidence of exclusive financial responsibility. The ruling strengthens doctrinal support for equity-based asset distribution in divorce cases Keywords: Joint Property, Legal Protection for Wife, Divorce, Economic Contribution, Court Decision.